Criminal liability for crimes committed under the influence of alcohol: public opinion - Irina Grigorievna Ragozina; Mihail Sergeevich Kuzyukov (Сибирское юридическое обозрение, 2011)
The article examines public opinion about the need to enforce criminal responsibility for crimes committed under the influence of alcohol.